2016
DOI: 10.1017/ice.2016.242
|View full text |Cite
|
Sign up to set email alerts
|

Status of the Prevention of Multidrug-Resistant Organisms in International Settings: A Survey of the Society for Healthcare Epidemiology of America Research Network

Abstract: OBJECTIVE To examine self-reported practices and policies to reduce infection and transmission of multidrug-resistant organisms (MDRO) in healthcare settings outside the United States. DESIGN Cross-sectional survey. PARTICIPANTS International members of the Society for Healthcare Epidemiology of America (SHEA) Research Network. METHODS Electronic survey of infection control and prevention practices, capabilities, and barriers outside the United States and Canada. Participants were stratified according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The secondary hospitals included in our study did not have an IPC team as developed as the one in the tertiary hospital in India. The study in India also found participants reporting the availability of IPC supplies but experiencing challenges with compliance, while an international study of healthcare settings representing 30 countries identified inadequate supplies as a barrier to infection control of multidrug resistant organisms in some high and middle income countries [13,14].…”
Section: How Results Relate To Other Studiesmentioning
confidence: 99%
“…The secondary hospitals included in our study did not have an IPC team as developed as the one in the tertiary hospital in India. The study in India also found participants reporting the availability of IPC supplies but experiencing challenges with compliance, while an international study of healthcare settings representing 30 countries identified inadequate supplies as a barrier to infection control of multidrug resistant organisms in some high and middle income countries [13,14].…”
Section: How Results Relate To Other Studiesmentioning
confidence: 99%
“…However, while these rapid‐identification methods have yielded some gains, they are often limited in their speed by the need to first culture specimens and limited in their utility by only providing species‐level classifications. Strain‐level discrimination is not only vital information for infection control teams in their efforts to determine if an outbreak is occurring, but could also be utilized in guiding treatment decisions, as certain lineages have the strong associations with resistance and virulence phenotypes . Despite our incomplete understanding of the genetic mechanisms of virulence and resistance for prominent pathogens, genome‐guided methods hold great promise as rapid clinical diagnostics with the potential to reduce turnaround times for organism identification and susceptibility testing, as well as aid infection‐prevention investigations, by providing the ultimate resolution for determining relatedness of strains in healthcare settings.…”
Section: Clinical Diagnosticsmentioning
confidence: 99%
“…FMT is a very promising therapy for decolonization and infection prevention, but it will be operationally challenging to use FMT as a prophylactic therapy on all patients who are at risk for infection. Currently, surveillance for presence of certain pathogens is performed in some institutions for some pathogens, but it is far from wide-spread [28]. It is logistically challenging to screen all patients for even a fraction of the pathogens they might be colonized with.…”
Section: Introductionmentioning
confidence: 99%